Nurses' experiences of managing patient deterioration following a post-registration education programme: A critical incident analysis study. (January 2018) - Butler, Clare
Abstract: The aim of this study was to explore nurses' experiences assessing and managing deteriorating patients in practice following completion of a relevant post-registration education programme. Recognising the increasing acuity of ward patients, nurses are faced with patients who are at an increased risk of deterioration. Patients who are acutely ill or deteriorating often exhibit periods of physiological deterioration; however there is evidence illustrating that these clinical changes are frequently missed, misinterpreted or mismanaged in practice. In order to prepare nurses to competently assess and manage the deteriorating patient, education as a care initiative is offered to develop the knowledge and skills required. A qualitative study using critical incident analysis was conducted to acquire narrative data from nurses, describing their clinical practice experiences of patient deterioration. Thematic analysis was used to analyse the data. Findings revealed improvements in nurses' abilities to recognise patient deterioration, greater application of the evidence base and an increase in confidence and assertiveness. There was some evidence of applying the knowledge and skills learned, however equally some nurses indicated that they remained ill-prepared to apply the skills in practice. Highlights: Post-registration education has potential to improve care of deteriorating patients. Nurses reported improved knowledge and skill acquisition following formal education. Better recognition of deterioration cues, attributed to the education programme. Nurses' reported increased confidence asserting deterioration in practice.